Carbon storage variability in seagrass meadows of Marine Poton Bako, East Lombok, West Nusa Tenggara, Indonesia - FIRMAN ALI RAHMAN; IBNUL QAYIM; YUSLI WARDIATNO (Biodiversitas Journal of Biological Diversity, 2018)
Rahman FA, Qayim I, Wardiatno Y. 2018. Carbon storage variability in seagrass meadows of Marine Poton Bako, East Lombok, West Nusa Tenggara, Indonesia. Biodiversitas 19: 1626-1631. The increase of atmospheric CO2 concentration in the last decades leads to global warming, having an adverse effect on the environment condition on the Earth. One of the natural mechanism as an effort to reduce the impact of global warming is carbon absorption and storage through photosynthesis mechanism of seagrass vegetation. Research conducted at Poton Bako, a district in East Lombok was aimed to reveal the composition of seagrass species, density, seagrass coverage, the biomass of seagrass tissue, content of carbon storage in seagrass tissue (above and below substrates), carbon content in seagrass sediments, and estimation of carbon stock in the area. The research included observation of species composition, and the sample was collected from 0.5 m × 0.5 m plot area. The total plot area was 36 on six lanes with the space between plots 25 m and between lanes 100 m. Six species from two families were found in the seagrass meadows, i.e., Cymodocea rotundata, Enhalus acoroides, Halophila minor, Holodule uninervis, Thalassia hemprichii and Thalassodendron ciliatum. The three highest total densities were C. rotundata 214.67±110.469 stands m-2, T. hemprichii 85.11±41.471 stands m-2, and H. minor 42.22±44.204 stands m-2. Species with the highest coverage value at all observation plots was C. rotundata (33.47±26.748 %), and T. ciliatum had the lowest value (2.12±5.071 %). The total biomass was 676.32 g DW m-2 with biomass above substrate 329.94±57.725 g DW m-2 and below substrate 654.88±81.199 g DW m-2. The carbon content of substrate ranged from 0.11% to 0.51% with the average of 0.35±0.081%, which was categorized low. The total average of carbon storage in seagrass was 447.92 g C m-2 comprising 142.77 g C m-2 of their tissue above substrate and 305.15 g C m-2 below substrate. Regarding the area, the total carbon stored in seagrass meadows with 56.65 ha area was 249.27 t C ha-1.